Case report: Radiofrequency ablation combined with biopsy for Cushing’s syndrome due to ectopic ACTH lesions in the lung - Zhang, Xiao; Meng, Liangliang; Xiao, Yueyong; Chen, Zenan (Frontiers in Oncology, 2022)
Lung carcinoid tumor is one of the major tumors causing ectopic ACTH syndrome, and the most common clinical treatment is surgical resection of the lesion. We herein report a suspected pulmonary carcinoid tumor with difficulty in surgical resection and poor response to drug therapy, which was successfully treated with radiofrequency ablation combined with intraoperative biopsy of the lesion. A 48-year-old female patient, with hypercortisolism (reddening of the face, full moon face, hirsutism, acne, and weight gain) detected three months ago. Small and high-dose dexamethasone suppression tests were not suppressed, Cushing's syndrome was under consideration. PET-CT examination suggested mild FDG uptake in two nodules in the anterior basal segment of the lower lobe of the right lung, the possibility of ectopic ACTH lesions was considered because of the clinical presentation. Due to difficult surgical approach of the lesion, high risk of surgery and the patient's anxiety, CT-guided thermal ablation combined with puncture biopsy was considered to treat the lesions. Image-guided thermal ablation can effectively inactivate ectopic ACTH lesions in the lung, rapidly improve the symptoms of high cortisol, and can be combined with biopsy for pathologic diagnosis. Therefore, this technique can be considered for treating pulmonary ACTH lesions that are difficult to resect surgically.